Perioperative pain management of orthopaedic patients based on new guidelines and literature review - Neścior-Piech, Małgorzata; Orzeł, Anna; Piech, Piotr; Janeczko, Dominika; Miziak, Paulina (Journal of Education, Health and Sport, 2019)
The pain management is an important issue of orthopedics and traumatology. The choice of therapy should be based on proper assessment of pain, monitoring and appropriate selection of analgesics. The necessary knowledge about the pharmacokinetic and pharmacodynamic profile of the drugs allows to maximize the benefits and minimize the risks associated with the use of painkillers and The proper pain management affects the time between surgical intervention and rehabilitation. In spite the of new analgesics and broadening knowledge about the mechanisms of pain, the results of treatment are unsatisfactory. Growing addiction to opioids is a major concern. A multimodal approach to pain management can provide better pain control and reduced opioid consumption. The purpose of this article was to review of the latest literature and recommendation to provide a summary of effective perioperative analgesic methods.